Subcutaneous implants for long-acting drug therapy in laboratory animals may generate unintended drug reservoirs - Michael Guarnieri; Betty M Tyler; Louis DeTolla; Ming Zhao; Barry Kobrin (Wolters Kluwer Medknow Publications, 2014)
Background: Long-acting therapy in laboratory animals offers advantages over the current practice of 2-3 daily drug injections. Yet little is known about the disintegration of biodegradable drug implants in rodents. Objective: Compare bioavailability of buprenorphine with the biodegradation of lipid-encapsulated subcutaneous drug pellets. Methods: Pharmacokinetic and histopathology studies were conducted in BALB/c female mice implanted with cholesterol-buprenorphine drug pellets. Results: Drug levels are below the level of detection (0.5 ng/mL plasma) within 4-5 days of implant. However, necroscopy revealed that interstitial tissues begin to seal implants within a week. Visual inspection of the implant site revealed no evidence of inflammation or edema associated with the cholesterol-drug residue. Chemical analyses demonstrated that the residues contained 10-13% of the initial opiate dose for at least two weeks post implant. Discussion: The results demonstrate that biodegradable scaffolds can become sequestered in the subcutaneous space. Conclusion: Drug implants can retain significant and unintended reservoirs of drugs.